Duality for frames in Krein spaces - Giribet, Juan Ignacio (2018)
A J-frame for a Krein space H is in particular a frame for H (in the Hilbert space sense). But it is also compatible with the indefinite inner-product of H, meaning that it determines a pair of maximal uniformly definite subspaces, an analogue to the maximal dual pair associated with an orthonormal basis in a Krein space. This work is devoted to study duality for J-frames in Krein spaces. Also, tight and Parseval J-frames are defined and characterized.